Effects and determinants of cross-order mergers and acquisitions (CBMAS) in five east asian countries/ Song Saw Imm… [et.al.] - Song, Saw Imm; Abdul Rahman, Rashidah; Kueh, Chiok Choo; Chu, Ei Yet (2010)
Cross-border Mergers and acquisitions (CBMAs) form a large portion of foreign direct investment flows in developed world, and an increasing share in emerging markets especially to the Asian countries after Asian Financial Crisis in 1997/98. Various studies have been done on wealth effects and financial performance of firms in different countries and have yielded mixed results. This study covers CBMAs in five Asian countries most affected by the Asian financial crisis namely, Malaysia, Thailand, Indonesia, the Philippines, and Korea. Malaysia reported the highest number of CBMAs but a rather low percentage of CBMAs in proportion to total M&As. The majority of the CBMAs in these countries were in the financial sector, followed by the industrial and material sectors.